2018
DOI: 10.1182/blood-2018-99-115509
|View full text |Cite
|
Sign up to set email alerts
|

BET Inhibitors Potentiate Activation of p53 and Killing of AML By MDM2 Inhibitors — a Candidate Combination Therapy

Abstract: In 2016, there will be approximately 19,950 new cases of Acute Myeloid Leukaemia (AML) in the United States. After diagnosis, five-year survival is currently ~26%, with available therapeutic approaches. Therefore, there remains a critical requirement for novel therapies for AML. Bromodomain and extra-terminal domain inhibitors (BETi) are emerging as exciting therapeutic agents for haematopoietic malignancies, including AML. The BET protein family, BRD2, BRD3, BRD4 and BRDT, are best known as tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We also found that tumor suppressor p21, the downstream effector and cooperator of p53, was upregulated with 100 nM of ZBC260 and 24 h treatments (Figure S1H,I). These results were consistent with those of the previous studies, ,, verifying the reliability of DIA-MPP for studying PROTAC efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that tumor suppressor p21, the downstream effector and cooperator of p53, was upregulated with 100 nM of ZBC260 and 24 h treatments (Figure S1H,I). These results were consistent with those of the previous studies, ,, verifying the reliability of DIA-MPP for studying PROTAC efficacy.…”
Section: Resultsmentioning
confidence: 99%